The Future of Technology and Robotics in Surgery - Ismael Domínguez-Rosado; Miguel A. Mercado (Permanyer, 2021)
In the past three decades, several technologies designed for other purposes, have been applied in surgery to provide more precision to the surgical procedures and better outcomes. In surgery, innovation requires evidence before widespread implementation of novelties and a continuous quality improvement process to assess benefits and risks. Robotics in surgery has been widely implemented, but in some cases, there are many doubts regarding its clinical benefit and cost utility. The future of surgery lies in the fulfillment of four main conditions: safety, access, efficiency, and efficacy. Innovation and technology should help to accomplish these conditions, but it must not be the center of surgical practice. We present here our perspective on the main issues related to technology and robotics focusing on evidence-based surgery.